Pengaturan Pernikahan Anak di Bawah Umur dalam Hadis dan Hukum Islam - Habibi. H; Amrudin (Al Fuadiy Jurnal Hukum Keluarga Islam, 2025)
Child marriage remains a debated issue in Islamic legal discourse due to the absence of an explicit minimum age requirement in hadith and classical fiqh. This article examines the regulation of underage marriage through an analysis of prophetic traditions, classical and contemporary juristic opinions, and developments in modern Islamic legal thought using a qualitative normative library research approach. The study finds that Islamic teachings emphasize readiness, capability, and responsibility rather than numerical age, while simultaneously upholding the principle of preventing harm. Through a maqāṣid al-sharī‘ah perspective, contemporary Islamic law increasingly views child marriage practices that cause physical, psychological, and social harm as inconsistent with the objectives of protecting life, intellect, and lineage. These findings contribute to a contextual understanding of hadith and support the formulation of Islamic legal regulations oriented toward child protection and public welfare.